Seleção de bases de dados eletrônicas para aplicação da técnica forward snowballing para apoiar a atualização de estudos secundários - Silva, Anderson Yoshiaki Iwazaki da (2018)
Context: Secondary studies should be updated from time to time to include new evidence to preserve their value. It is recognized that one search technique to update secondary studies is forward snowballing and that the number of studies identified is dependent on the electronic database selected. However, there is no consensus on which database is most appropriate for applying forward snowballing. Objective: The main goal of this study is to evaluate the use of different electronic databases for applying forward snowballing to update secondary studies. Method: Six updates were performed using forward snowballing with support from two electronic databases, one specific and the other generic. Results: When using a specific database, there is a risk of missing relevant studies. More studies are read and included with generic database adoption, however, there is no guarantee that all relevant studies will be detected. Conclusions: A single database, whether generic or specific, does not return all relevant studies in updating context. One strategy is to combine electronic databases to prevent the loss of evidence.